Characteristics and Chemical Composition of Fly Ash From Pulang Pisau’s Power Plant as A Potential Material for Synthesis of Aluminosilicate Materials - Rendy Muhamad Iqbal; Akhmad Damsyik; Retno Agnestisia; Siswo Siswo (Jurnal Sains dan Terapan Kimia, 2022)
The Steam-Electric Power Station (PLTU) is one of the initiatives to meet the nation's current electricity requirements. The use of fuel for steam power plant is still dominated by fossil fuels such as coal. Even though domestic energy needs are met, steam power plant turns out to be a contributor to gas emissions that cause global warming, as well as a by-product in the form of fly ash which can cause environmental and ecosystem problems. Fly ash contains silica oxide (SiO2) and aluminum oxide (Al2O3) compounds which can be used as raw materials for synthesizing aluminosilicate-based materials such as geopolymers and zeolites. This study tested the characteristics and composition of chemical compounds in fly ash from Pulang Pisau’s power plant, Central Kalimantan. Characterization using X-Ray Diffraction (XRD) showed that peaks of quartz material dominated fly ash from Pulang Pisau’s power plant at 2θ=20.82°;26.61° and mullite minerals at 2θ= 31.2°;33.1°; 35.4°;39.2°;59.8°. The results of the chemical compound composition were tested using the ASTM-D3682-12 standard. Fly ash has a composition of 29.00% SiO2, 9.98% Al2O3, 13.75% Fe2O3, and 28.37% CaO. Fly ash from Pulang Pisau’s power plant is classified as type C fly ash, which can potentially be used as a source of aluminosilicate-based material synthesis.